An application of hypergeometric shift operators to the $𝜒$-spherical Fourier transform - Ho, Vivian M.; Ólafsson, Gestur (Trends in Harmonic Analysis and Its Applications, 2015)
We study the action of hypergeometric shift operators on the Heckman-Opdam hypergeometric functions associated with the